Low Energy Laser Treatments Control Annual Ryegrass (Lolium rigidum) - Coleman, Guy; Betters, Christopher; Squires, Caleb; Leon-Saval, Sergio; Walsh, Michael (Frontiers in Agronomy, 2021)
Increasing concern for the ongoing availability and efficacy of herbicides is driving interest in the development of alternative physical and thermal weed control methods. Fortunately, improvements in weed detection through advancements in computing hardware and deep learning algorithms are creating an opportunity to use novel weed control tools, such as lasers, in large-scale cropping systems. For alternative control options, there are two key weed control timing opportunities, early and late post-crop emergence. Weed density for the early timing is typically higher, with a shorter window for control. Conversely, late post-emergent treatment of surviving and late-emerging weeds would occur in lower densities of larger and more variably sized weeds, given a prior weed control effort, but with a longer available weed control period. Research in laser weeding to date has primarily focused on early growth stage weeds and the ability of this approach to control larger weeds remains unknown. This study used a 25 W, 975 nm fiber-coupled diode laser to evaluate the opportunity for control of annual ryegrass (Lolium rigidum Gaudin) and the influence of four different growth stages (three-leaf, seven-leaf, mid-tillering and late-tillering). Annual ryegrass plants at each growth stage were treated using a laser-focused to a 5mm diameter with five different irradiation durations developing energy densities of 1.3, 2.5, 6.4, 19.1 and 76.4 J mm-2. At the three-leaf stage, all plants were controlled at 76.4 J mm-2 and 93.3% controlled at 19.1 J mm-2. Complete control of seven-leaf plants was only achieved at 76.4 J mm-2. Although laser treatments did not control mid-tillering stage plants, 76.4 J mm-2 reduced biomass by 60.2%. No similar reductions in biomass were recorded for the largest plants. This initial research assists in the development of novel weed control options in the context of large-scale conservation cropping systems. Future research should investigate additional species and increased laser powers to reduce treatment durations and increase the size of weeds controlled.